The potential of high heat generating granites as EGS source to generate power and reduce CO2 emissions, western Arabian shield, Saudi Arabia. (December 2015) - Chandrasekharam, D.; Lashin, A.; Al Arifi, N.; Al Bassam, A.; El Alfy, M.; Ranjith, P.G.; Varun, C.; Singh, H.K.
Abstract: Saudi Arabia's dependence on oil and gas to generate electricity and to desalinate sea water is widely perceived to be economically and politically unsustainable. A recent business as usual simulation concluded that the Kingdom would become an oil importer by 2038. There is an opportunity for the country to over come this problem by using its geothermal energy resources. The heat flow and heat generation values of the granites spread over a cumulative area of 161, 467 sq. km and the regional stress regime over the western Saudi Arabian shield strongly suggest that this entire area is potential source of energy to support 1) electricity generation, 2) fresh water generation through desalination and 3) extensive agricultural activity for the next two decades. The country can adopt a policy to harness this vast untapped enhanced geothermal systems (EGS) to mitigate climate and fresh water related issues and increase the quantity of oil for export. The country has inherent expertise to develop this resource. Highlights: Total electricity generated by Saudi Arabia is 271 TWh. Additional 134 × 106 kWh is consumed for desalination. Saudi Arabia's current status of electricity generation and desalinate sea water is perceived to be unsustainable. The country has sizable reserves of EGS resources to mitigate these issues. Per capita CO2 emission of 16 Mt can be saved. Country can provide power, water and food security by adopting EGS technology.